(untitled) (Eurasian Research Bulletin, 2023)
The article analyzes the place of women in the society, the attention paid to them in our country, and the fact that their place is incomparable in the upbringing of the young generation and the future generation. Also, the impact of the family environment on the new generation and its ability to find its place in the society is detailed.